Area of residual tumor is a robust prognostic marker for patients with rectal cancer undergoing preoperative therapy. Issue 3 (3rd March 2018) - Sakuyama, Naoki; Kojima, Motohiro; Kawano, Shingo; Matsuda, Yoko; Mino‐Kenudson, Mari; Ochiai, Atsushi; Ito, Masaaki
Abstract : The aim of this study was to elucidate differences in the histological features of rectal cancer between patients treated with preoperative chemoradiotherapy and those treated with preoperative chemotherapy. Area of residual tumor (ART) was also evaluated for its utility as a potential prognostic marker between them. Sixty‐eight patients with rectal cancer who underwent sphincter‐saving surgery were enrolled in this study. Of these, 39 patients received preoperative chemoradiotherapy (CRT group) and 29 patients received preoperative (neoadjuvant) chemotherapy (NAC group). Area of residual tumor was determined by using morphometric software. Tumors in the two groups were compared for differences in their histological features and clinical outcomes. Tumors in the CRT and NAC groups varied greatly with regard to their histological features after preoperative therapy. Tumors in the CRT group showed more marked fibrosis than those in the NAC group. The total ART were significantly smaller in tumors in the CRT group than those in the NAC group. However, in circumferential resection margin‐negative pathologic stage 0‐III cases, clinical outcomes were not statistically different between the CRT and NAC groups. Both ART and pathologic TNM classification were associated with clinical outcome in preoperative CRT and NAC groups, but Dworak regression grade and fibrotic change were not. Tumors in those undergoing preoperative CRT and NAC were shown to differ significantly in their histological features. Area of residual tumor‐based assessment may provide useful prognostic information, regardless of preoperative therapy. Abstract : The aim of this study is to elucidate differences in histological features between patients with rectal cancer receiving preoperative chemoradiotherapy and chemotherapy. Area of residual tumor (ART) was also evaluated for its ability to estimate prognosis in these patients. Finally, our findings suggest that our proposed ART‐based assessment may provide useful prognostic information regardless of preoperative therapy.